Why are Aspen Extractives More Resistant in Kraft Pulping Than Pine Extractives? - Shin, Soo-Jeong; Ahn, Sye-Hee (목재공학, 2006)
We investigated why aspen extractives are more resistant in kraft pulping than pine extractives. Residual extractives content in aspen kraft pulps were 0.5~1.1% compared with 0.1~0.2% in pine pulps. This different response arises from the different composition of extractives in wood chips. Resin acids in pine were almost completely removed in kraft pulping but those are not existence in aspen. Slower saponification of aspen steryl esters resulted from different chemical structure of aspen steryl esters. Main sterols in aspen steryl esters were 24-methyl cyclolanostenol which was highly resistant to alkaline hydrolysis with its characteristic steric hindrance. Sterols in aspen were not well removed in kraft pulping. The relative composition of sterol in aspen kraft pulps was increased with increasing pulping time. The presence of fatty acids in aspen kraft pulps is considered to unusual. Fatty acids in alkaline are supposed to be well ionized and removed well in the washing stage. Nevertheless, there were significant amount of fatty acids remaining in aspen kraft pulps.